2023
DOI: 10.1111/jace.19189
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric response and polarization mechanism of alkali silicate glasses in gigahertz to terahertz frequency range

Abstract: Oxide glasses are dielectric materials with potential applications in highfrequency communications; hence, their dielectric properties in the gigahertz to terahertz frequency range should be investigated. In this study, the dielectric properties of silica glass and five single alkali silicate glasses were measured at 0.5-10 THz using terahertz time-domain spectroscopy and far-infrared spectroscopic ellipsometry. At 0.5-10 THz, the silica glass exhibited low dielectric dispersion with a low dielectric constant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…In the GDMC-La glasses, the ε GHz increased from 4.66 to 4.93 with increasing the substitution of La 2 O 3 for (Al 2 O 3 + MgO), as shown in Figure 3 B. The ε GHz of the glasses mainly results from the polarizability contribution of their constituents [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Interestingly, with the incorporation of La 2 O 3 up to 0.8 mol%, ε GHz decreased by approximately 1 to 3% compared with that of the reference GDMC-Si59 glass.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…In the GDMC-La glasses, the ε GHz increased from 4.66 to 4.93 with increasing the substitution of La 2 O 3 for (Al 2 O 3 + MgO), as shown in Figure 3 B. The ε GHz of the glasses mainly results from the polarizability contribution of their constituents [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Interestingly, with the incorporation of La 2 O 3 up to 0.8 mol%, ε GHz decreased by approximately 1 to 3% compared with that of the reference GDMC-Si59 glass.…”
Section: Resultsmentioning
confidence: 93%
“…They found that the single- and co-doping of RE species can reduce the dielectric constant of the glasses because of the increase in the polymerization of the glass network structure. Several researchers have studied the dielectric responses and polarization mechanisms of alkali and alkaline earth-modified silicate glasses in the GHz–THz frequency range [ 7 , 9 , 10 , 11 , 12 , 14 ]. It was shown that the alkali-modified silicate glasses exhibit strong dielectric dispersion and show higher dielectric constants than the alkali-free glasses, which is due to the vibrations and migrations of alkali ions that are easily moved in the glass subjected to electromagnetic waves.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations